2012
DOI: 10.1186/1741-7015-10-114
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on the role of treatment-related HIV compensatory mutations on increasing virulence: new discoveries twenty years since the clinical testing of protease inhibitors to block HIV-1 replication

Abstract: Approximately 20 years has passed since the first human trial with HIV-1 protease inhibitors. Protease inhibitors set the stage for combination therapy in the mid-1990s but are now rarely used in first-line combination therapy and reserved for salvage therapy. Initially, resistance to protease inhibitors was deemed unlikely due to the small enzymatic target with limited genetic diversity, the extended drug binding site in protease, and the need to cleave multiple sites in the HIV-1 precursor proteins. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These mutations are found in individuals who have transmitted drug resistance, but they are not common in the treatment-naive HIV-1 population. One suggestion is that the evolutionary pathway to this polymorphism is simply too complex to emerge de novo [81], suggesting that the virus has evolved into a region of genetic space from which there is no return.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations are found in individuals who have transmitted drug resistance, but they are not common in the treatment-naive HIV-1 population. One suggestion is that the evolutionary pathway to this polymorphism is simply too complex to emerge de novo [81], suggesting that the virus has evolved into a region of genetic space from which there is no return.…”
Section: Discussionmentioning
confidence: 99%
“…However, when correcting for such bias, increased prevalence of polymorphisms under drug pressure is observed across all subtypes and robust associations with known resistance mutations support their involvement in viral evolution during treatment [6,7]. We recently reported that a higher number of polymorphic compensatory mutations, previously described to be selected during treatment, correlated with higher estimated in vivo fitness, higher plasma HIV--1 RNA levels and lower CD4+ T--cell lymphocytes in drug--naive patients [11,12]. These findings are supported by studies reporting a wide range of in vitro replication capacity values in drug-naive patients and that improved replication capacity increases the virulence of HIV--1 [13].…”
Section: Textmentioning
confidence: 96%
“…Additionally, in the absence of virus phenotyping, we are unable to determine whether the two DRMs that occurred in such low frequency in IVR-wearing animals were, in fact, from infectious viruses. If so, their replicative fitness compared to wt virus would be interesting to determine since some HIVs with DRMs may have attenuated growth [47] , [48] and then acquire compensatory mutations that restore fitness [49] , [50] .…”
Section: Discussionmentioning
confidence: 99%